Students' and Teachers' Perceptions About Hospital Educational Environment In Selected Postgraduate Medical Institutes of Bangladesh - Alo, Dilara; Talukder, Md Humayun Kabir; Rahim, Riffat (Bangladesh Journal of Medical Education, 2018)
This descriptive type of cross sectional study was carried out to observe the hospital educational environment of selected postgraduate medical institutes of Bangladesh. Study period was from July 2016 to June 2017.Sample size was 289 postgraduate clinical students of various course (MD, FCPS & Diploma) and 20 clinical teachers of 10 selected postgraduate medical institutes of Bangladesh. Convenience sampling technique was adopted. Data collection was done with self- administered semi-structured questionnaire using Postgraduate Hospital Educational Environment Measurement (PHEEM) inventory and by In-depth interview of teachers. Three subscales of PHEEM are students' perceptions about 'role autonomy', students' perceptions about quality of teaching and students' perceptions about social support. In-depth interview of the clinical teachers was undertaken to explore the training facilities in the selected postgraduate medical institutes of Bangladesh. Study result revealed total PHEEM score was110.08.Mean score of subscales of PHEEM were 34.51, 36.29 and 26.28 for 'role autonomy', quality of teaching and social support respectively. All these values indicates that the students' perception were in the right or positive direction. Analysis of individual items had shown mean score of most of the individual item were 2-3 that indicated the aspects of the climate that could be enhanced. There were few items that had mean score 2 or less than 2 that indicated the problematic areas of hospital educational environment. In-depth interview of the teachers revealed that there was also some problematic issues on postgraduate training facilities like work overload, lack of proper monitoring or supervision of training, inadequate library, internet, ICU and investigation facilities etc. Study recommended that significant attention should be paid in the problematic areas (lack of supervised training, heavy work load of student, lack of library facility etc.) as well as improvement needed on several areas of hospital educational environment of postgraduate medical institutes of Bangladesh. Bangladesh Journal of Medical Education Vol.9(1) 2018: 7-9